Family measurement techniques abstracts of published instruments, 1935 - 1974 - Straus, Murray A. 1926-2016; Brown, Bruce W. (Univ. of Minnesota Press, 1978)
813 measurement techniques, arranged and described under various aspects of family life, e.g., husband-wife relationships. 130 journals and pertinent books used as sources. Each entry gives test name, variables measured, length, availability, and references. Author, test title, and subject indexes.